A rare vaginal birth after four caesarean sections: a case report of a rural area - Azam Khattak, Sumaira (Journal of the Pakistan Medical Association, 2025)
Vaginal Birth after Caesarean section (VBAC) is an approach to promote normal deliveries and decrease the growing inclination towards Caesarean Section (CS). Attempts at normal vaginal deliveries are now considered conclusive for proceeding in women with a history of caesarean section. Although there are potential risks involved, clinical practice often favours repeat caesarean sections. This case report highlights a prospective approach towards the normal vaginal delivery in patients with a history of multiple CS. This case report describes a rare case of a 32 -year-old patient with four previous caesarean sections, who was admitted as an emergency case at the government hospital, District headquarters Landikotal, Peshawar, District Khyber. She had no scheduled antenatal care, and no previous antenatal records were available. Despite this, she experienced a spontaneous advanced vaginal delivery. There were no signs of previous caesarean scar rupture, and full dilatation of 10cm was achieved. Keywords: Normal vaginal delivery (NVD), vaginal birth after Caesarean-section (VBAC), caesarean section (CS), lower uterine segment (LUS), Appearance, Pulse, Grimace, Activity and Respiration (Apgar score).